Introduction: The Teaching of Philosophy at Universidad Nacional (UNA), Costa Rica - Gómez Torres, Juan (2018)
First of all, we would like to express our deep gratitude to Gabriela D'Odorico and Alejandro Cerletti for their time, their willingness, and their valuable contributions to discuss and complement the philosophical-pedagogical training that Professor Juan Gómez, who was the spark that ignited our interest in critical-transformative pedagogy, which he took pains to provide us with during our two years as active students of the bachelor's in the Teaching of Philosophy at the Center for Research and Teaching in Education (CIDE in Spanish). Without you, none of this would be possible.